Study of Serum Lipid Profile in Patients with Beta-Thalassemia Major - H. N. Khan, A. R. Shinde, Swati Choudhary, A.M. Siddiqui (International Journal of Innovative Research in Medical Science, 2016)
Introduction: Beta-thalassemia is an inherited blood disease characterized by inadequate production of haemoglobin, globin subunits, ineffective hematopoiesis, and increased hemolysis. Objective: The aim of the study was to examine the serum lipid profile in patients with beta-thalassemia major, and to determine the factors that affect it. Material and methods: The study comprises a total of 80 subjects between age group 4 to 14 years including patients with beta-thalassemia major (n=40) and controls (n=40). Blood samples were collected and serum was separated to be tested for serum total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol and serum triglycerides was done by Erba XL-640 fully automated analyser. Results: Significant changes confirmed that lipid abnormality occur in beta-thalassaemia major patients when total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol and serum triglycerides levels compared with healthy subjects. Conclusion: Our results revealed that lipid profile changed in patients with beta-thalassemia major. Many factors such as iron overload, liver injury, hormonal disturbances and aging might cause these changes.